Analisis Pemberdayaan Masyarakat Desa Dalam Kemandirian Dan Pembangunan Di Kecamatan Jambi Luar Kota - Nopyandri Nopyandri; A Zarkasi; Dimas Rizal (LP2M, 2020)
The purpose of this study was to determine the role of the village government of Jambi luar kota in empowering rural communities in rural independence and development. As we know, The Village autonomy is genuine, round, and complete autonomy and is not a gift from the government. Instead, the government is obliged to respect the original autonomy held by the village. As a form of democracy, a village consultative body was formed in the village which functioned as a legislative and supervisory body for the implementation of village regulations, village income and expenditure budgets, and village head decisions. The village budget includes original village income, APBN allocation known as the Village Fund, part of the district/city revenue and tax, village fund allocation which is part of the balance funds received by the district/city, financial assistance from the provincial APBD and district / APBD cities, grants and non-binding donations from third parties. With so many funds for village development above, can the village government implement an independent village development and support the village development program launched by the central government or vice versa. This study was conducted using a qualitative research approach. This research was conducted in Jambi Luar Kota and in Muaro Jambi Regency. The results of this study found that the empowerment of Village Communities in Self-Reliance and Development in Jambi Luar Kota District even though it has been done, the results are not yet optimal. it is due to several factors: 1). Communication Factors, 2). Organizational structure.